Implementasi QRCode Untuk Absensi Perkuliahan Mahasiswa Berbasis Paperless Office - Ifriandi Labolo (Universitas PGRI Semarang, 2019)
Attendance recording or more commonly known as presence. Presence is one of the important factors in the field of education. The implementation of the current and current presence system at STMIK Ichsan Gorontalo still uses a lot of paper so that the possibility of being scattered or lost can occur. The paperless reduction campaign in an agency both public and private is being intensified to reduce the impact of deforestation to produce paper or tissue. Therefore, the use of paper especially in educational institutions should be reduced or eliminated. This research took the idea of utilizing QR-Code and Android OS Smartphone to become a mobile-based presence system that supports the paperless office.